Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1074/jbc.m312791200
|View full text |Cite
|
Sign up to set email alerts
|

A Cellular UDP-glucose Deficiency Causes Overexpression of Glucose/Oxygen-regulated Proteins Independent of the Endoplasmic Reticulum Stress Elements

Abstract: A low level of UDP-Glc occurs in cells exposed to hypoxia or glucose starvation. This work reveals that a 65% reduction in the cellular UDP-Glc level causes upregulation of the mitochondrial chaperone GRP75 and the endoplasmic reticulum (ER) resident chaperones GRP58, ERp72, GRP78, GRP94, GRP170, and calreticulin. Conditions that cause misfolding of proteins within the ER activate the transcription factors ATF6␣/␤ and induce translation of the transcription factors XBP-1/ TREB5 and ATF4/CREB2. These transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 72 publications
1
28
0
Order By: Relevance
“…It has also been reported that CRT overexpression stimulates the proteasomal degradation of SERCA (sarcoplasmic/endoplasmic reticulum Ca 2ϩ ATPase) under oxidative stress (43). Although further investigations may be needed to clarify this hypothesis, it is likely that under a stress condition in which CRT is up-regulated (25,26), CRT may be expressed at the cell surface and interact with CFTR, which may stimulate the endocytosis of CFTR and direct it to proteasomal degradation. Recently (during the preparation of this manuscript), it was reported that oxidant stress suppresses CFTR expression (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that CRT overexpression stimulates the proteasomal degradation of SERCA (sarcoplasmic/endoplasmic reticulum Ca 2ϩ ATPase) under oxidative stress (43). Although further investigations may be needed to clarify this hypothesis, it is likely that under a stress condition in which CRT is up-regulated (25,26), CRT may be expressed at the cell surface and interact with CFTR, which may stimulate the endocytosis of CFTR and direct it to proteasomal degradation. Recently (during the preparation of this manuscript), it was reported that oxidant stress suppresses CFTR expression (44).…”
Section: Discussionmentioning
confidence: 99%
“…Some CRT is expressed at the cell surface and in the extracellular environment, although it is most abundantly expressed in the ER (19,24,25). Moreover, CRT is up-regulated in response to various types of ER stress (26), which induce conformational change of CRT leading to enhanced interaction with its substrates (25). Thus, CRT may have a role distinct from CNX in the quality control of CFTR, although the role of CRT in the quality control of CFTR remains unknown.…”
mentioning
confidence: 99%
“…All tissue culture reagents were obtained from Gibco/Invitrogen, and all other reagents were obtained from Sigma, unless otherwise indicated. sis, exposure to free radicals, and hypoxia can interfere with protein folding and lead to the accumulation of misfolded or unfolded proteins in the lumen of the ER, causing ER stress that activates the unfolded protein response (UPR) [13][14][15]. The initial aim of UPR is to restore normal function of the cell, however, if the damage is too severe to repair, the UPR ultimately initiates cell death through activation of the apoptotic pathway [16].…”
Section: Methodsmentioning
confidence: 99%
“…This is part of the ER machinery that imports proteins from the secretory pathway into the ER, and together with other chaperones such as 78-and 94-kDa glucose regulated proteins (GRP 78 and GRP 94) ORP 150 assists in the folding and assembly of secretory and membrane proteins [13]. The expression of ORP 150 becomes increased in a range of pathologic situations such as brain ischaemia [14], atherosclerotic plaques [15] and malignant tumours [16].…”
Section: Introductionmentioning
confidence: 99%